TABANNI SEBAGAI HALUAN GERAKAN HIZBUT TAHRIR INDONESIA - Arif Gunawan Santoso (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
Nowadays, it is found a negative stigma facing Islamic fundamentalism. However Indonesian Hizbut Tahrir (HTI) still exists and has strong influence. This organization is different from the others. It does not have regional or national figures. This research applies quantitative approach and has purpose to discover the factors that increase its influences despite having negative stigma and rejection. Framing theory is conducted to analyze the data and result. The result shows that HTI is not same with the other organizations that have leaders to drive their followers. HTI emphasizes on the tabanni idea and thought to drive their followers.